The impact of the affordable care act on breast cancer care in the USA: A multi‐institutional analysis. Issue 5 (11th June 2019) - Maxwell, Jessica; Shats, Oleg; Aldridge, Joshua; Lyden, Elizabeth; Krie, Amy; Conklin, Richard; Manning, Kenneth; Fahed, Rabih; Vaziri, Irfan; Deveras, Ruby Anne E.; Mateen, Zubeena; Crow, Kate; et al.
Abstract: There are less data available on the effect of the ACA on breast cancer care beyond the screening level. A retrospective review at participating iCaRe2/BCCR institutions was completed before and after ACA. Post‐ACA, patients were older, more urban, and more likely to be insured through Medicaid. Increased imaging use was noted post‐ACA. These patients were less likely to be diagnosed with late‐stage cancers, received fewer mastectomies, and were more likely to have radiation.